LIFESTYLE DAN KESEJAHTERAAN: POTRET MATA PENCAHARIAN PADA MASYARAKAT PESISIR LOMBOK UTARA - Hafizah Awalia; Arif Nasrullah; I Dewa Made Satya Parama (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study explores the transformation of lifestyle and well-being in Gili Air’s coastal community, North Lombok, driven by rapid tourism growth. Using a qualitative case study approach with in-depth interviews, participatory observation, and document analysis, it uncovers socio-economic change patterns. Findings show tourism has shifted livelihoods from traditional fishing and dryland farming to service jobs like homestays, tour guiding, and souvenir trading, boosting income, promoting modern consumption (gadgets and branded goods), and improving material well-being. However, this threatens local customs, social structures, and cultural values, seen in declining communal solidarity (gotong royong) and rising individualism, plus environmental strains from overdevelopment like land conversion and beach erosion, risking long-term sustainability. Referencing Jean Baudrillard, the study highlights the paradox: economic gains often foster illusory prosperity via symbolic consumption. Solutions involve multi-stakeholder collaboration based on local wisdom and participation to create inclusive policies for sustainable development, cultural preservation, and equitable benefits, ensuring modernization maintains ecological and social balance.